Talbot holographic effect in scientific holomovie - Ismanov, Y.H.; Sagynbaev, A.A. (Recent Contributions to Physics, 2015)
The article deals with the Talbot effect in its holographic manifestation. Ordinary Talbot effect is known well. However, its properties in holography not been investigated. In the article presents the results of such researches. Analytically shown that the reproduction of the hologram of one-dimensional linear grating, in addition to the emergence of virtual and real images of the grating in the three diffraction orders restores the sequence of their self-reproductions also. And all of these sequences extend to the space of real images that allows you to watch them without the use of special optics. On the basis of established effect authors developed a model of unique multi-channel wide-range holographic interferometry having four output channels with different sensitivity. The paper presents the results obtained on a computer model of the interferometer. This interferometer is able to operate in real time. This fact allows to receive interference patterns in all channels of the interferometer. The patterns vary according to changes in the characteristics of the studied dynamic phase medium. In other words, the proposed interferometer allows you to record the dynamics of changes in the phase medium under consideration in three-dimensional format, i. e. we have holomovie in this case.